The influence of the hydrogenation degree on selected properties of graphene as a material for reversible H2 storage. (30th August 2019) - Kaczmarek, Ł.; Warga, T.; Zawadzki, P.; Makowicz, M.; Bucholc, B.; Kula, P.
Abstract: This article discusses the effect of hydrogenation of graphene (one-sided and two-side hydrogenation) in relation to the change in the physicochemical properties of graphane as a material capable of reversible H2 storage. Therefore, the change of the system's energy was determined, differences in HOMO-LUMO molecular levels and the distribution of electrostatic potential as a function of its hydrogenation were simulated. At the same time, the mechanism of graphane reduction to graphene was discussed as a result of interaction with steam from the air. It has been shown that along with the increase in the degree of hydrogenation, the graphane changes its electrostatic potential from negative to positive, simultaneously pushing the negative charge to the edge of the graphene flake. This fact may have an impact on its further chemical reactions, which may significantly limit the sorption properties of graphene. Areas rich in negative charge will prefer chemical reactions with molecules of electrophilic properties, while positive areas with molecules of nucleophilic properties. This determines the elimination of the storage environment of graphene structures used as reversible sources of chemical bonding of hydrogen in order to increase their lifetime as well as sorption capacity. Highlights: Changes in graphene related to the amount of adsorbed hydrogen are investigated. Transition between graphene and graphane is examined using modelling software. Possible application of graphene in energy storage industry is explained. One-sided and completely two-sided hydrogenation of graphene is considered.